A rare case of unilateral lymphoid papillary hyperplasia of tonsil in a nine-year-old girl - Narang, Ekta; Gupta, Aarshi; Khatri, Arti; Jain, Neha; Tyagi, Sonali; Chaudhary, Dimple (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
We report a rare case of lymphoid papillary hyperplasia of palatine tonsil in a 9-year-old girl. It is a rare benign pathology characterised by papillomatous appearance of palatine tonsil with reactive lymphoid hyperplasia. Early recognition of this lesion is important because in spite of clinical feature being suggestive of malignant tumour, it is a benign tumour-like proliferation, that can easily be cured by tonsillectomy.